Sistem Informasi Geografis Pemetaan Lokasi Sekolah di Wilayah Kecamatan Wewewa Tengah dengan Menggunakan Metode Arcview GIS - Pora, Estiana Astuti; Neno, Friden Elefri; Ege, Emirensiana Dappa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The most crucial area that needs to be addressed in order to raise the standard of human resources is education. Wewewa Tengah sub-district has a vast selection of schools, allowing parents and other young kids to pick one that best matches their needs. Many parents are unaware of where to find information about a school's profile and location, which makes it challenging for parents to select a school for their children. The objective of this research is to create a website-based Geographic Information System that allows for the collecting of school data starting in kindergarten and continuing through middle school, high school, and vocational school. This app encourages users to look up local schools and offers details on each institution's point coordination system. This application is intended to make it simpler for the general public to learn where schools are located and when they start in Central Wewewa. A linear-sequential technique (Waterfall) was utilized to construct the system, and a number of components, including HTML, PHP, and MySQL, were utilised. The key advantage of this study is webgis that can provide school locations and start times in the Central Wewewa community. The study's findings suggest that WebGIS makes it simpler to produce maps, that the system can display locations on a map and information about school locations, and that the system can function effectively.Keywords: Geographic information system, Mapping, WebGIS